Pengaruh Moral Kognitif Pada Kinerja Keperilakuan Dan Kinerja Hasil Tenaga Penjualan - Ribhan Ribhan; Nasrullah Yusuf (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
Ethical decision making has become a critical issue as the pressure to improve the behavior of successful salespeople in all the current economic conditions. The values contained in the employees will affect the decision making of individuals or employees that will have an impact on organizational performance. Moral or cognitive moral is at the core of the most ethical decision-making models in the marketing and management. This study examined the effect of cognitive moral behavioral performance and  outcome performance of the sales force and influence behavioral performance in sales force outcome performance. By using simple linear regression method obtained  results that the  hypothesis that cognitive moral effect on behavioral performance of salespeople, singnifikan effect (b = -0.296; sig 0.000) supported. Hypothesis 2 is not supported, which suggests that moral considerations affect the outcome performance in this study were not significant (b = -0.122; sig .148). The next hypothesis states that behavioral performance positive influence on the outcome  performance of the support (b = 0.217; sig 0.009). To obtain the results of an individual's performance is good and responsible, it must enhance or improve the behavior of decision-making is based on cognitive moral salespeople. Performance results of the sales force increased when the behavior of salespeople work better and responsible.